Light dark matter in a gauged U(1)L[my]-L[tau] model - Foldenauer, Patrick (Physical review, 2019)
As experimental null results increase the pressure on heavy weakly interacting massive particles (WIMPs) as an explanation of thermal dark matter (DM), it seems timely to explore previously overlooked regions of the WIMP parameter space. In this work we extend the minimal gauged U(1)Lμ−Lτ model studied in [M. Bauer, P. Foldenauer, and J. Jaeckel, J. High Energy Phys. 07 (2018) 094.] by a light (MeV-scale) vectorlike fermion χ. Taking into account constraints from cosmology, direct and indirect detection we find that the standard benchmark of MV=3mχ for DM coupled to a vector mediator is firmly ruled out for unit DM charges. However, exploring the near-resonance region MV≳2mχ we find that this model can simultaneously explain the DM relic abundance Ωh2=0.12 and the (g−2)μ anomaly. Allowing for small charge hierarchies of ≲O(10), we identify a second window of parameter space in the few-GeV region, where χ can account for the full DM relic density.
Gesehen am 15.08.2019
Im Titel sind [my] und [tau] als griechische Buchstaben dargestellt
Im Titel ist L[my]-L[tau] tiefgestellt